Quality Indexes of Warehouse Services - Oláh, Judit (International Journal of Engineering and Management Sciences, 2016)
There was a wide range and rapid development in the field of warehouse management in the recent decades as a result of strong and spectacular improvement of establishing and operating warehouses, in addition to increasingly complex logistic processes. In my research, I analysed the complex problems of determining the performance expectedfromoperatingthewarehousetechnologicalsystem. Thisdecisioninvolvestheselection of the essential performance indicators suitable for performance measurement and the determination of the expected performance level based on these indicators through the example of an examined enterprise. During my research, I concluded that the logistic performance measurement of warehouse processes is a very difficult process, because all enterprises have to define and use indexes which adapt to the enterprise profile well and reflect the performance to be measured. This decision is of key importance, since the warehouse system and its operation principles have to be adjusted to this expected performance.